Second Fundamental Theorem of Calculus
![Second Fundamental Theorem of Calculus Video](https://cdn-academy.pressidium.com/academy/wp-content/uploads/2023/01/circle-play-duotone.png)
Hello and welcome to this video about the Second Fundamental Theorem of Calculus! We will explore what this part says and how it works, but first a refresher of the First Part:
If f(x) is continuous on [a,b] and \(\int f(x)dx=F(x)\) on [a,b], then
\(\int_a^bf(x)dx=F(b)-F(a)\)
Let’s get right to it! The Second Part of the Fundamental Theorem of Calculus (It’s got ‘Fundamental’ in its name, so you know it’s important – in fact, it’s perhaps the most important in calculus!) is closely related to the first and says:
If f(x) is is continuous on [a,b] and the function F(x) is defined by
\(F(x)=\int_a^xf(t)dt\)
then F'(x)=f(x) over [a,b].
The biggest implication with this part is that it guarantees that every integrable function has an antiderivative. Notice how F(x) is defined as an integral function – x can be any value and the function will return a number. This is what’s called an accumulation function.
Let’s see how this part of the theorem works!
Suppose \(g(x)=\int_1^xf(t) dt\). Use the given values of F(t) to evaluate g(x).
F(0)=0 F(1) =2 F(2)=-3 F(4)=5
x | g(x) |
0 | \(\int_1^0f(t) dt=F(0)-F(1)=-2\) |
1 | \(\int_1^1F(t) dt=0\) |
2 | \(\int_1^2f(t) dt=F(2)-F(1)=-5\) |
4 | \(\int_1^4f(t) dt=F(4)-F(1)=3\) |
Let’s try another one!
If \(hx=\int_2^x(3t^2+4t)dt\), then, by the theorem, we know \(h’x=3x^2+4x\). Notice the derivative function is expressed in terms of x instead of t, since the integral function is a function of x.
Why is this true? Well, let’s take a look!
\(h(x)=\int_2^x(3t^2+4t)dt\)
=\(t^3+2t^2|_2^x\)
=\((x^3+2x^2)-(2^3+2(2)^2\)
=\(x^3+2x^2-16\)
Therefore, \(h’x=3x^2+4x\).
This is especially powerful with more complex antiderivatives like this:
If \(r(x)=\int_3^x\frac{\sqrt{t}}{t^2-3}dt\), then \(r'(x)=\frac{\sqrt{x}}{x^2-3}dx\)
Let’s get a little practice in.
If \(g(x)=\int_{-5}^{2x}(t^2-t-3)dt\), find a formula for g(x) and calculate g'(x).
\(g(x)=\frac{1}{3}t^3-\frac{1}{2}t^2-3t|_{-5}^{2x}\)
\(g(x)=(\frac{8x^3}{3}-\frac{4x^2}{2}-6x)-(-\frac{125}{3}-\frac{25}{2}+15)\)
\(g(x)=\frac{8x^3}{3}-\frac{4x^2}{2}-6x+\frac{235}{6}\)
\(g'(x)=8x^2-4x-6\)
Suppose \(g(x)=\int{-2}^{x}f(t) dt\). Use the provided values of F(t) to evaluate g(x).
F(-1)=6 F(-5)=0 F(2)=10 F(-2)=4
x | g(x) |
-1 | \(\int_{-2}^{-1}f(t) dt=F(-1)-F(-2)=6-4=2\) |
-5 | \(\int_{-2}^{-5}f(t) dt=F(-5)-F(-2)=0-4=-4\) |
2 | \(\int_{-2}^{2}f(t) dt=F(2)-F(-2)=10-4=6\) |
I hope that this video helped with your understanding of the Second Fundamental Theorem of Calculus!
If you enjoyed this video then be sure to give us a thumbs up, and subscribe to our channel for further videos.
See you next time!